PENERAPAN METODE KETELADANAN OLEH GURU UNTUK MENANAMKAN NILAI-NILAI PENDIDIKAN KARAKTER SISWA DALAM PEMBELAJARAN AQIDAH AKHLAK DI MIS AT-TAQWA SAMBAS - Heni Pratiwi; Rusiadi Rusiadi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This research started from looking at the phenomenon that occurred at MIS At-Taqwa Sambas where some students were lacking in instilling character education values ​​so that they did not match the expectations of the teacher. Therefore, the aqidah moral teacher tried to instill character education values. The subjects of this study were teachers of aqidah morality, principals, students. To obtain data related to the research focus, the researcher conducted interviews, observations and documentation. The implementation of the teacher's example in instilling the values ​​of character education in the learning of moral aqidah at MIS Sambas is guiding, evaluating, cooperating, motivating, evaluating. Then evaluate the application of the teacher's example in instilling character education values ​​in moral aqidah learning at MIS At-Taqwa Sambas, namely providing guidance to students, collaborating between teachers and parents, motivating students by giving stories that inspire students, conduct extracurricular activities, evaluate the activities that have been carried out. The supporting and inhibiting factors for implementing the teacher's example in instilling the values ​​of character education in learning moral aqidah at MIS At-Taqwa Sambas are a) Supporting factors; provide guidance for fardhu prayers, provide role models, healthy physical or spiritual conditions of students, family conditions that care about students' Islamic religious education, cooperation between teachers, school principals and parents of students. b) Inhibiting factors; students are less enthusiastic to follow the guidance of the teacher, facilities and infrastructure are still minimal, there are some parents who do not cooperate in fostering student morals, low parental Islamic religious education, lack of parental support.